1994
DOI: 10.3109/10611869408996813
|View full text |Cite
|
Sign up to set email alerts
|

The Use of Phospholipid Liposomes for Targeting to Oral and Skin-Associated Bacteria

Abstract: Phospholipid (dipalmitoylphosphatidylcholine (DPPC) plus phosphatidylinositol (PI)) proteoliposomes with surface bound lectins (succinylated concanavalin A (s con A) and wheat germ agglutinin (WGA)) have been prepared covering a range of size and surface density of lectin. Negatively charged phospholipid liposomes from DPPC-PI mixtures covering a range of PI mole % and positively charged liposomes from DPPC-cholesterol-stearylamine (SA) mixtures covering a range of SA mole % have been prepared. The targeting o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

1996
1996
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 23 publications
(10 citation statements)
references
References 19 publications
0
10
0
Order By: Relevance
“…In addition to known methods of targeting drugs to cells, including antibody, protein or peptide, liposomal, and magnetic targeting [4350], use of ultrasound affords a direct and exact focusing on the treated site. Nonactivated PS does not harm healthy tissues.…”
Section: Resultsmentioning
confidence: 99%
“…In addition to known methods of targeting drugs to cells, including antibody, protein or peptide, liposomal, and magnetic targeting [4350], use of ultrasound affords a direct and exact focusing on the treated site. Nonactivated PS does not harm healthy tissues.…”
Section: Resultsmentioning
confidence: 99%
“…Phosphatidylinositol and stearylamine are known targeting ligands for several oral and skin associated bacteria (see also 3.1). [75,76,84,86] It was observed with TEM that both types of liposomes cluster around the bacteria in a similar way. [83] They also studied the binding of anti-S. oralis immunoliposomes and found that the immunoliposomes were located on the surface of the bacterial cells with a preference for the septal region between dividing cells.…”
Section: Studying the Interaction And Transport Of Nanoparticles In Bmentioning
confidence: 91%
“…Examples of organisms for which this targeting was less effective are S. epidermidis and P. vulgaris. [84,86] This is likely due to the absence of the binding site for Con-A.…”
Section: Specific Targetingmentioning
confidence: 99%
See 1 more Smart Citation
“…Intra-periodontal pocket drug delivery systems are highly desirable due to a potentially lower incidence of undesirable side-effects, improved therapeutic efficacy, easy application and increased patient compliance. They can be made biodegradable and non-immunogenic and cost effective [169,170]. Vesicular systems are designed to mimic the bio-membrane in terms of structure and bio-behavior, and hence are investigated intensively for targeting bacterial biofilms [169,171].…”
Section: Intra-periodontal Targetted Pocket Drug Deliverymentioning
confidence: 99%